"This is a Pakhtun disease": Pakhtun health journalists' perceptions of the barriers and facilitators to polio vaccine acceptance among the high-risk Pakhtun community in Pakistan. Issue 28 (19th June 2019) - Shah, Sayyed Fawad Ali; Ginossar, Tamar; Weiss, David
Abstract: Introduction: Pakistan is one of only three poliomyelitis-endemic countries in the world. Twelve wild poliovirus (WPV) cases were recorded in the country in 2018. Even though resistance to oral polio vaccine (OPV) has decreased over time, there are still pockets of communities, mostly ethnic Pakhtun living in the Khyber Pakhtunkhwa (KP) province, that resist OPV. Although local journalists may be important sources of health information, past studies have overlooked their role in this context. The purpose of this study was to examine Pakhtun health journalists' beliefs regarding OPV and their views of the barriers and facilitators that influence OPV acceptance or hesitancy in their communities. Methods: We recruited and interviewed 33 Pakhtun journalists covering health issues for diverse media outlets in high-risk districts for WPV of the KP province. The semi-structured interviews were translated, transcribed, and analyzed for themes. Results: The participants strongly supported OPV and advocated that children in their own families and communities get vaccinated against polio. At the same time, they felt that their communities faced more urgent health needs that were not addressed by the government. They identified barriers at the media organizational level operating against accurate coverage of OPV, including financial and time constraints, a lack of checks and balances, and limited health literacy. They regarded press releases issued by the officials associated with OPV campaigns as the main facilitators in the coverage of OPV. The participants perceived lack of community trust in the government, security concerns, and community members' religious beliefs as the major impediments to increase in uptake of OPV. Conclusion: Pakhtun health journalists have the potential to be important partners in national polio eradication initiatives. They should receive culturally sensitive training in local languages at appropriate literacy levels. We also suggest direct involvement of journalists in community mobilization efforts.